ANALISA PENGARUH BRAND (AWARENESS, ASSOCIATION & IMAGE) DAN PERCEIVED (QUALITY & VALUE) TERHADAP PURCHASE INTENTION MELALUI PERAN MEDIASI BRAND LOYALTY - Fresha Febri Yunus; Ronny Firdiansyah Arief (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract : This study aims to determine the influence of brand and perceived that affect the purchase intention of a smartphone brand in Batam City which is mediated by brand loyalty. This study focuses on taking samples of consumers who have the intention to buy smartphone brands from Iphone, Vivo, Oppo, Xiaomi, and Samsung. The findings in the study were conducted on 309 respondents who are interested in buying a smartphone brand. The data analysis method used in this study through Partial Least Square Structural Equation Modeling (PLS_SEM) with the help of the SmartPLS Version 3.0 program. The results show that brand loyalty, brand association, and brand image significantly affect purchase intention, while brand awareness, perceived quality, and perceived value did not significantly affect purchase intention. Furthermore, the results showed that brand awareness, brand image, and perceived value had a direct and significant effect on brand loyalty. The remaining variable brand association, perceived quality, has no significant effect on brand loyalty. For indirect testing, it was found that brand awareness, brand image, and perceived value can have a better effect on purchase intention through brand loyalty mediation.